2017
DOI: 10.7554/elife.30523
|View full text |Cite
|
Sign up to set email alerts
|

53BP1 and BRCA1 control pathway choice for stalled replication restart

Abstract: The cellular pathways that restart stalled replication forks are essential for genome stability and tumor prevention. However, how many of these pathways exist in cells and how these pathways are selectively activated remain unclear. Here, we describe two major fork restart pathways, and demonstrate that their selection is governed by 53BP1 and BRCA1, which are known to control the pathway choice to repair double-strand DNA breaks (DSBs). Specifically, 53BP1 promotes a fork cleavage-free pathway, whereas BRCA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 63 publications
9
73
1
1
Order By: Relevance
“…Further, our results indicate that the RAD51-dependent, strand exchange-dependent mechanism is more predominant after 8 hours of exposure to HU as compared to 5 hours of exposure, while the converse is true for the RAD51-dependent, strand exchange-independent mechanism. These data are consistent with a previous study that identified an early, cleavageindependent restart pathway involving 53BP1 and a late, HR-dependent pathway involving BRCA1 48 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Further, our results indicate that the RAD51-dependent, strand exchange-dependent mechanism is more predominant after 8 hours of exposure to HU as compared to 5 hours of exposure, while the converse is true for the RAD51-dependent, strand exchange-independent mechanism. These data are consistent with a previous study that identified an early, cleavageindependent restart pathway involving 53BP1 and a late, HR-dependent pathway involving BRCA1 48 .…”
Section: Discussionsupporting
confidence: 93%
“…This observation suggests that replication fork remodeling mediated by hsRAD51-II3A traps replication restart intermediates that cannot be resolved by RAD51 strand exchange-independent pathways. The partial dependency of 53BP1 foci on MUS81 suggests that a major fraction of the trapped intermediates are collapsed forks, but it is possible that the processing of unbroken reversed forks is also blocked by RAD51-II3A, given prior evidence that 53BP1 can localize to replication forks prior to DSB formation 44,48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 However, 53BP1 has been implicated in additional PARPi-relevant contexts, such as at the replication fork. [38][39][40] The finding that REV7 is also required for the resistance caused by TIP60 depletion supports a mechanism involving activity at the double-strand break; 41 however, other potential roles for REV7 at the replication fork have not yet been thoroughly characterized. 42 Therefore, other function(s) of 53BP1/REV7 may potentially be involved in the rescue of PARPi-induced cytotoxicity downstream of TIP60 depletion in BRCA2-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…(9)'daki ζ ifadesi, l 1 /l 2 -kaideleri arasındaki ödünleşime karşılık gelmektedir [16]. Eger ζ çok büyük ise l 1 -kaideli ifadeyi vurgulamaktadır.…”
Section: Introductionunclassified